The Marketing Mix Effect on Purchase Decisions of Anandia Bakery in Padang City - Fauzi, Dian; Leovita, Angelia; Agia, Nur Willa (Jurnal Dinamika Sosial Ekonomi, 2025)
Rapid changes and growth in the business sector in the era of globalization are marked by increasing competition, including among the 28 small bakery businesses operating in Padang City. Anandia Bakery is one of the oldest MSMEs in the local bakery industry and continues to operate today. This study aims to: (1) describe the business profile of Anandia Bakery; (2) analyze consumer perceptions of purchasing decisions; and (3) examine the influence of the 4P marketing strategy on purchasing decisions. The study employs a quantitative descriptive approach using multiple linear regression analysis. The results show that (1) Anandia Bakery was established in 2006, employs eight workers, and operates four days per week; (2) consumer perceptions of product, price, and distribution are very positive, falling into the “Strongly Agree” category; and (3) product (X1), price (X2), and distribution (X4) have a significant effect on purchasing decisions. In contrast, the promotion variable (X3) has no significant effect, indicating that current promotional efforts are not yet effective in influencing consumer decisions. These findings confirm that product quality, competitive pricing, and ease of distribution are the main factors driving consumer purchasing decisions.